Identification of Important Performance Metrics of Different Routing Protocols in the context of Different Scenarios using ANOVA Test - Babu, Ch Suresh; Gangadhara Rao, K; Basaveswara Rao, B; Chandan, K (International Journal of Computer Sciences and Engineering, 2019)
In this paper, the performance metrics of routing protocols by varying node density and transmission range are analyzed using the statistical tool called Two-way ANOVA. The performance of routing protocols namely AODV, DSR, DSDV and OLSR are evaluated in two different traffic classes using NS2 simulation study. The sample data is collected from this simulation study. The Quality of Service metrics such as PDR, NRO, E2ED, TP and Jitter are treated as dependent variables which are evaluated by varying independent factors namely Node Density and Transmission Range. The ANOVA test is intended to ratify the correctness of the results and to investigate the important metrics while using individual factors and interaction effect between factors. The results of the ANOVA test found to be inline with that of NS2 simulation.